Legal Opinion : Peracunan Eks Spionase Rusia - Amanda Eugenia Soeliongan (CV Rewang Rencang, 2020)
The poisoning of Sergei Skripal in Britain by Russian military intelligence drew widespread condemnation from various countries in the world. This action violates state sovereignty and violates International Law because the assassination attempt uses chemical weapons, a nerve agent from the Soviet era named Novichok. Britain finally responded strongly by designating 23 Russian ambassadors as Persona Non-Grata, which was in accordance with the provisions of the 1961 Vienna Convention on Diplomatic Relations. Persona Non-Grata as the exclusive right of any State that can be used as a sanction if there is a violation of international law, although there may be arbitrary in its use because the Receiving State is not obliged to give a valid reason. Therefore, Persona Non-Grata in diplomatic law may be used as a warning or instrument of interruption for a diplomatic relationship that is considered incompatible. This paper will discuss the incident in the review of International Diplomatic and Consular Law.